Construction of Sensor for Submicromolar Detection of Riboflavin by Surface Modification of SPCE with Thermal Degradation Products of Nickel Acetate Tetrahydrate. Issue 9 (18th March 2022) - Ognjanović, Miloš; Stanković, Dalibor M.; Jaćimović, Željko K.; Kosović‐Perutović, Milica; Mariano, José F. M. L.; Krehula, Stjepko; Musić, Svetozar; Antić, Bratislav
Abstract: Nickel acetate tetrahydrate (NAT) sample series were used to modify screen‐printed carbon electrodes (SPCE). The samples were hybrid Ni/NiO nanocomposites, where the NiO phase increased with an applied treatment temperature. Results of electrochemical measurements pointed that the Ni/NiO550 /SPCE‐modified electrode had the best analytical performance toward the detection of riboflavin (RF). The Ni/NiO550 /SPCE‐based sensor showed linear response with RF in the concentration range of 0.5–75 μM and 0.15 μM LOD in BRBS. Sensor offered fast response time, good repeatability, and selectivity with an RSD of 1.4 %. Our results show that the Ni:NiO nanocomposite ratio strongly influenced the electroanalytical performance of SPCE. Abstract :